Research of the technique of percussion massage in the training day of high-qualified rowers of academists - Artemenko, E.P.; Miftakhov, S.F. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to investigate the effect of a short-term percussion massage session on anaerobic power and external respiration parameters in qualified rowers. Methods and structure of the study. The study involved 12 male athletes specializing in rowing. The participants ranged in age from 18 to 22 years old. The athletes' athletic qualifications ranged from II adult category to master of sports. All the athletes were in the preparatory phase of their annual training cycle and had no injuries or medical contraindications. The total duration of the percussion massage session was 2 minutes and 15 seconds. The protocol included sequential exposure to the muscles of the back (60 seconds), neck (15 seconds), and arms (15 seconds each). The choice of these muscle groups was based on their active participation in the stroke phase. Results and conclusions. The data obtained clearly demonstrate the improvement of almost all key power characteristics after massage effect. After the percussion massage session, there was a statistically significant increase in anaerobic performance indicators. The time to reach peak power and gas exchange indicators did not show significant changes. Improved strength performance may be associated with neuromuscular activation, improved local blood flow, and reduced muscle stiffness.